2020
DOI: 10.1371/journal.pone.0236838
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic contamination of drinking water: A systematic review

Abstract: Background Microplastics (MPs) are omnipresent in the environment, including the human food chain; a likely important contributor to human exposure is drinking water. Objective To undertake a systematic review of MP contamination of drinking water and estimate quantitative exposures. Methods The protocol for the systematic review employed has been published in PROSPERO (PROSPERO 2019, Registration number: CRD42019145290). MEDLINE, EMBASE and Web of Science were searched from launch to the 3rd of June 2020, sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
101
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 225 publications
(108 citation statements)
references
References 92 publications
5
101
0
2
Order By: Relevance
“…S5a, b (OR2) where we can see that there is only a weak negative trend between the size of the identified MP and the content in the samples which could be attributed to the small number of studies and other confounding parameters previously discussed. The association between the size of the measured MPs particles and their content has already been highlighted in our previous work [85]. Fragment was the most commonly discovered shape of MPs across all studies, followed by fibre (Table 2).…”
Section: Statistical Summary Of Effects/narrative Analysissupporting
confidence: 66%
“…S5a, b (OR2) where we can see that there is only a weak negative trend between the size of the identified MP and the content in the samples which could be attributed to the small number of studies and other confounding parameters previously discussed. The association between the size of the measured MPs particles and their content has already been highlighted in our previous work [85]. Fragment was the most commonly discovered shape of MPs across all studies, followed by fibre (Table 2).…”
Section: Statistical Summary Of Effects/narrative Analysissupporting
confidence: 66%
“…2019 ), whereas in our previous work, salt was found to have an MP content of ( Danopoulos et al. 2020a ), tap water , and bottled water ( Danopoulos et al. 2020b ).…”
Section: Discussionmentioning
confidence: 67%
“…A recent study by Guillen et al (2019) attempted to calculate the global seafood production and consumption footprint using FAO consumption data and modeling, reporting China to be the major global producer and consumer and also as being self-sufficient for the most part (Guillen et al 2019). Other media have also been identified as vectors of MPs via the ingestion route with varying MP concentrations, such as sugar (0:44 MPs=g) (Cox et al 2019), whereas in our previous work, salt was found to have an MP content of 0-1,674 MPs=kg (Danopoulos et al 2020a), tap water 0-628 MPs=L, and bottled water 0-4,889 MPs=L (Danopoulos et al 2020b). Further systematic reviews are needed to robustly assess MP contamination and human exposures from all food categories.…”
Section: Discussionmentioning
confidence: 68%
“…Danopoulos and colleagues also recently published systematic reviews of microplastics exposure from salt 6 and drinking water. 7 They estimated potential human exposures via salt at 0–6,110 MPs/year. 6 For drinking water, they estimated that people might be consuming up to 458,000 MPs/year for tap water and 3,569,000 MPs/year for bottled water, based on average water consumption.…”
mentioning
confidence: 99%
“… 6 For drinking water, they estimated that people might be consuming up to 458,000 MPs/year for tap water and 3,569,000 MPs/year for bottled water, based on average water consumption. 7 “The results of all three systematic reviews,” Danopoulos says, “can be used in an aggregate exposure framework from all three mediums, which will give us an estimate of high confidence on human microplastics exposures.”…”
mentioning
confidence: 99%